Prolong and Break: Experiences from an Itinerant Improvisation Workshop in Mexico - Terrazas, Wilfrido (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
This article discusses the author's journey of facilitating improvisation workshops in Mexico, starting in 2007. The text first provides personal context, as well as context related to the emergence of a local improvised music scene in Mexico City in the 2000s. The text goes on to expound the underlying ideas that function as guidelines for the workshop, and the various strategies that it employs in its ever-changing methodology. Originally written in Spanish, this English version includes a new section that provides follow-up reflections four years after writing the original text was written.